INDUSTRI PALEOLITIK PADA ENDAPAN ALLUVIAL KALI MARON (PACITAN, JAWA TIMUR) BERDASARKAN ANALISIS RETUS - Driwantoro, Dubel; Semah, Francois; Purnomo, Andri (Berkala Arkeologi, 2001)
Kali Maron is an archaeological site whose artifatcs are no longer insitu, because sedimentological analysis has proven that its lithic artifacts are the result of river sediment. The location of the Maron River which is very close to the sea (downstream), does not allow a clear geomorphology of the terraces: lithic artifacts are found on the river bed. However, the large amount of artifact content in the sediment (7, 7% of the total composition) makes the Maron river a very rich site. The existence of these artifacts that have never been disturbed makes the Maron industry quite representative from a statistical point of view. The alluvial matrix of the artefacts previously described (disctance of transportation before deposition) also means significant proportions, where the Maron river site fully reflects the exploitation of lithic artifacts in the surrounding area.